Digging Deeper: Bioturbation increases the preserved sulfur isotope fractionation - Riemer, Sydney; Turchyn, Alexandra V.; Pellerin, André; Antler, Gilad (Frontiers in Marine Science, 2023)
Bioturbation enhances mixing between the seafloor and overlying ocean due to changes the redox state of the sediment and influences the biogeochemical cycling of redox-sensitive elements such as sulfur. Before the widespread appearance of burrowing fauna over the Proterozoic-Phanerozoic transition, marine sediments were largely undisturbed and transport of material across the sediment-water interface was diffusion-dominated. Through both a microcosm experiment and numerical model, we show that the effect of bioturbation on marine sediments is to enhance the drawdown of sulfate from the water column into the sediment and thus “open-up” the sedimentary system. The key finding is that bioturbation increases the difference between the isotopic signature of seawater sulfate and pore water sulfide, the latter of which is preserved in sedimentary sulfide minerals. Our study empirically demonstrates a long-held assumption and helps identify the isotopic impact of bioturbation in the geological record and its environmental effects in modern marine systems.